Teachers’ Perceptions of Conservation Education and Its Implementation in Primary School Learning - Encep Andriana; Sholeh Hidayat; Suroso Mukti Leksono (Journal of Educational Studies, 2026)
Conservation education in primary schools is seen as an important strategy for developing ecological understanding and environmental awareness through contextual, applied, and experience-based learning. The purpose of this study was to determine teachers' perceptions of conservation, teachers' perceptions of conservation education, and teachers' perceptions of conservation content based on local wisdom. The research method used mixed methods with a sequential exploratory mixed method type. This study consisted of 92 primary school teachers from various schools in Banten Province. The data collection techniques used in this study were questionnaires, interviews, observation, and documentation. The techniques used were descriptive quantitative analysis and thematic qualitative analysis. The results of this study revealed that teachers' perceptions of conservation showed a very high awareness of environmental conservation, teachers' perceptions of conservation education had been integrated into learning, but had not been implemented consistently, and teachers' perceptions of local-based conservation content were still limited and uneven. Based on the results of the study, it can be concluded that primary school teachers have a high awareness of environmental conservation, but the implementation of local-based conservation education in the classroom is still inconsistent and requires strengthening of competencies and support for contextual teaching materials.